Lava crickets (Caconemobius spp.) on Hawai'i Island: first colonisers or persisters in extreme habitats?. (13th January 2021) - Heinen‐Kay, Justa L.; Rotenberry, John T.; Kay, Adam D.; Zuk, Marlene
Abstract : 1. Primary succession after a volcanic eruption is a major ecological process, but relatively little is known about insects that colonise barren lava before plants become established. 2. On Hawai'i Island, the endemic cricket, Caconemobius fori Gurney & Rentz, 1978, is known as the first multicellular life form to colonise lava after an eruption from Kīlauea Volcano. In the Kona region, a congener, Caconemobius anahulu Otte, 1994 inhabits unvegetated lava flows from Hualālai Volcano, but little has been documented about its distribution. 3. Our aim was to characterise the presence/absence of Caconemobius spp . across lava flows that are largely unvegetated, but differ in age since eruption and connectivity to older flows. We used baited live traps to survey 9 month–50 year‐old Kīlauea lava flows for C. fori, and ∼220 year‐old Hualālai lava flows for C. anahulu . 4. We found no evidence that C. fori has colonised the Kīlauea flows from the 2018 eruption. However, we did discover that C. fori was persistent and widespread on Kīlauea lava up to 50 years old within Hawai'i Volcanos National Park. We also captured C. anahulu across much of the Hualālai lava flows we surveyed in Kona. 5. We demonstrated that C. fori do not always arrive on new lava within months after an eruption, in contrast to previous reports, and that both C. fori and C. anahulu can remain on lava longer than previously appreciated. Vegetation successional state may be more important than true age for the persistence of these endemic crickets. Abstract : We surveyed two wingless cricket species that are endemic to Hawai'i Island, Caconemobius fori and anahulu, across largely unvegetated lava flows of various ages. Contrary to previous predictions, we found no evidence that C. fori inhabit recent lava flows, likely due to dispersal limitation from lack of contiguous barren lava habitat. C. fori and C. anahulu were found on older lava than previously appreciated, suggesting that plant successional stage, rather than lava age, is key for cricket persistence.